Ductal carcinoma in situ on core needle biopsy only with no residual disease at surgery. Issue 6 (30th July 2018) - Dubrovsky, Esther; Nguyen, Pauline; Chun, Jennifer; Schwartz, Shira; Raymond, Samantha; Guth, Amber; Schnabel, Freya; Gerber, Naamit K.
Abstract: Background: The treatment of ductal carcinoma in situ (DCIS) remains controversial and may be particularly difficult for patients with minimal disease. There is a dearth of information regarding patients who have been diagnosed with DCIS on core needle biopsy (CNB), who have no residual disease in the lumpectomy specimen. The purpose of this study was to explore the frequency of this presentation and short‐term outcomes in these patients. Methods: Our institutional Breast Cancer Database was queried for all women who were diagnosed with pure DCIS from 2010 to 2016 and treated with lumpectomy. Variables included patient and tumor characteristics, adjuvant treatment, and ipsilateral breast tumor recurrence (IBTR). Statistical analyses included Pearson's chi‐square, Fisher's exact tests, and Kaplan‐Meier analysis. Results: Of 547 patients with pure DCIS, 50 (14%) had DCIS on CNB only. Of the patients with DCIS on CNB only, 15 were treated with lumpectomy and radiation therapy (RT), while 35 underwent lumpectomy without RT. At a median follow‐up of 4 years, there were 3 (6%) IBTR all within the same quadrant as the original lumpectomy site. None of the patients who recurred received adjuvant RT or hormonal therapy. Conclusions: Despite the minimal extent of disease exhibited in these cases, 6% of patients with DCIS on CNB only had IBTR at a median follow‐up of 4 years. These data suggest that even minimal DCIS represents a significant risk of recurrence to the patient. Size and margins are not sufficient criteria to stratify risk and guide decisions for adjuvant therapies.